The gut–kidney axis is regulated by astragaloside IV to inhibit cyclosporine A-induced nephrotoxicity - Han, Cong; Gao, Ran-ran; Zhou, Le; Li, Wei (Frontiers in pharmacology, 2025)
Chronic nephrotoxicity caused by CNIs (CICN) manifests clinically as chronic kidney disease (CKD). Astragaloside IV (AS-IV) plays a certain role in the treatment of CKD. This study aimed to verify the ameliorative effects of AS-IV on CICN and further explore the mechanisms underlying the modulation of the "gut-transcriptome-metabolome coexpression network" by AS-IV within the context of the "gut-kidney axis" to improve CICN. Five groups of 40 mice were studied: a normal group (N, olive oil), a model group (M, CsA, 30 mg kg d ), a low-dose AS-IV group (CsA + AS-IV, 30 mg kg d + 10 mg kg d ), a high-dose AS-IV group (CsA + AS-IV, 30 mg kg d + 20 mg kg d ), and a valsartan group (CsA + Val, 30 mg kg d + 10 mg kg d ). The gut microbiota, renal transcriptome, and urine metabolome were separately detected to construct a gut-transcriptome-metabolome coexpression network. The target species, target genes, and target metabolites of AS-IV were evaluated. CsA led to increased proteinuria and a deterioration of kidney function, accompanied by increased inflammation and oxidative stress, whereas AS-IV improved kidney damage. AS-IV inhibited intestinal permeability and disrupted the microbiota structure, increasing the abundance of , , , and Six coexpression pathways related to transcription and metabolism, including the , , , and , were identified. Seven target metabolites of AS-IV were identified in the 6 pathways, including UDP-D-galacturonic acid, 2-phenylethanol glucuronide, dehydroascorbic acid, isopentenyl pyrophosphate, alpha-D-glucose, 3-carboxy-1-hydroxypropylthiamine diphosphate and citalopram aldehyde. Five target genes of AS-IV, Ugt1a2, Ugt1a9, Ugt1a5, Pck1, and Slc7a11, were also identified and predicted by NONMMUT144584.1, MSTRG.30357.1 and ENSMUST00000174821. was highly correlated with renal function and the target genes and metabolites of AS-IV. The target genes and metabolites of AS-IV were further validated. AS-IV inhibited intestinal-derived urinary toxins and improved renal tissue apoptosis, lipid accumulation, collagen deposition, and mitochondrial damage. AS-IV improved CICN through the coexpression of the gut-transcriptome-metabolome network. The six pathways related to energy metabolism driven by , including the , , , , are important mechanisms.